2017
DOI: 10.22449/1573-160x-2017-2-11-18
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Principal Components of the Sea Ice Concentration Fields in the Barents Sea

Abstract: The processes of interaction within the ocean-sea ice-atmosphere system which influence a multiyear ice cover dynamics in the Barents Sea are investigated. Being analyzed, the principal components of the sea ice concentration fields in the Barents Sea make it possible to distinguish three modes of interannual variability of the sea ice concentration. It is shown that the first mode describes 65.4 % of the sea ice concentration total variance and its multiyear trend. The second mode (10.8 %) is related to the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…For this reason this part is not considered when comparing eddy areas. In 2011 the eddies are recorded northward than in 2007, due to the larger ice-free water region [15]. But on the whole, the situation of the eddy structure clusters is similar in the both years (as well as the regions with the highest occurrence, except for the southeastern part of the sea), and the general regularities within the season throughout the data array (Tab.…”
Section: Submesoscale Eddy Structuresmentioning
confidence: 87%
See 1 more Smart Citation
“…For this reason this part is not considered when comparing eddy areas. In 2011 the eddies are recorded northward than in 2007, due to the larger ice-free water region [15]. But on the whole, the situation of the eddy structure clusters is similar in the both years (as well as the regions with the highest occurrence, except for the southeastern part of the sea), and the general regularities within the season throughout the data array (Tab.…”
Section: Submesoscale Eddy Structuresmentioning
confidence: 87%
“…To detect small (submesoscale) eddy structures in the Barents Sea 1203 and 838 satellite SAR-images of ENVISAT ASAR respectively in June -October 2007 and 2011 in the C-band and WSM (swath width is 400 kilometers, a spatial resolution -150 m) and IMP (100 km and 25 m, respectively) shooting modes. The choice of 2007 and 2011 years is due to the fact that in these years the minimum ice area in the sea area was observed [15]. On average, the coverage of the Barents Sea was 120 images SAR mages, while in 2011 its southeastern part was not practically covered by SAR images.…”
Section: Methodsmentioning
confidence: 99%
“…It is apparent that, while the ice cover in the Arctic is retreating rapidly, the character of the changing ice is very different in the Atlantic and Pacific sectors [62][63][64][65]. A number of studies showed that the Barents Sea is one of the Arctic regions with the largest sea ice variability at different time scales [66][67][68] and the air-sea temperature differences in the Barents Sea are extremely large [69,70]. We can expect that sea ice change in the Barents Sea will greatly affect the heat release, thus affecting the local and possibly large-scale climatic conditions.…”
Section: Discussionmentioning
confidence: 99%